Pelestarian Koleksi Langka Berbasis Flipbook di Perpustakaan Umum - Rahayu, Ifon Margiati (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2021)
Introduction. Currently, the office limits access to collections of rare books for users to preserve the physical collection. Users who want to access the display will only get a synopsis. However, this policy makes users challenging to access the full-text content. The collection of rare books has also not received proper preservation and creates some rare book collections to be damaged. This study aims to determine the process of digitizing the rare book collections at the Archives and Library Office of Banjarnegara Regency based on Flipbook.Methodology. This study is a qualitative descriptive study. The selection of informants in this study is a purposive sampling technique. The data collection in this study is observation, interview, and literature study.Result and discussion. This study shows that digitizing the rare book collections includes selection, scanning, editing, flipbook making, and uploading on the OPAC INLISLite application 3.1. Users can access rare book collections in the form of flipbooks or interesting digital books. The obstacles found in digitizing rare book collections are the absence of SOPs of digitizing, inadequate digitization facilities and infrastructures, the absence of Human Resources (HR). Nevertheless, they master the digitization of collections and the lack of budget allocations for digitizing the collection.Conclusion. The impact of digitization with Flipbook is that users have full access to a collection of rare books needed by users and become an alternative to the preservation and empowerment of libraries and users that are more attractive and safe